Dmytro Ivanovych Kachenovskyi – a legal scholar, educator and teacher (based on the materials of Kharkiv Law Society) - O. K. Maliutina (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the scientific and pedagogical activities of the legal scholar, professor of Kharkiv University Dmytro Ivanovych Kachenovskyi (1827–1872). The researcher pioneered the national legal education and had a significant impact on its development. The study of the creative work of the mid-nineteenth century international law expert became relevant in the early twentieth century. In 1903, Kharkiv Law Society held a solemn meeting on the occasion of the 30th anniversary of Dmytro Kachenovskyi’s death. Following the meeting, a collection of materials in memory of Dmytro Kachenovskyi was published. These materials are a valuable historical source that contain special information and contribute to a deeper study of the scientist’s scientific heritage. The study of the source expands the existing documentary base. The purpose of the study is to study and analyse the materials of the collection published by the Kharkiv Law Society in honour of Professor Kachenovskyi.